Multilayered PtSe2/pyramid-Si heterostructure array with light confinement effect for high-performance photodetection, image sensing and light trajectory tracking applications. Issue 8 (2nd February 2021) - Ma, Mengru; Chen, Huahan; Zhou, Kunnan; Xie, Chao; Liang, Yi; Wang, Li; Wu, Chunyan; Yang, Wenhua; Guo, Jiawen; Luo, Linbao
Abstract : A multilayered PtSe2 /pyramid-Si heterostructure-based photodetector array consisting of 8×8 device units shows excellent optoelectrical performance with potential applications in NIR image sensing and real-time light trajectory tracking. Abstract : Two-dimensional layered (2D) materials are currently attracting intensive research interest for high-performance photodetection and other optoelectronic applications. However, the study of device integration for multifunctional optoelectronic applications is still at a nascent stage. Here, the assembly of a multilayered PtSe2 /pyramid-Si heterostructure-based photodetector array consisting of 8 × 8 device units is demonstrated. Owing to the pronounced light confinement effect of the heterostructures, the devices present an prominent photovoltaic effect, which enables efficient self-driven photodetection in a broadband wavelength spectrum. The I light / I dark ratio, responsivity, external quantum efficiency (EQE) and specific detectivity can attain values as high as 5.51 × 10 6, 567 mA W −1, 87% and 1.26 × 10 13 jones, respectively, upon 810 nm near-infrared (NIR) light illumination. What is more, benefiting from the large-scale homogeneous material growth technique, the photodetector array exhibits excellent uniformity and repeatability in photoresponse performance with negligible unit-to-unit variation. The above characteristics provide the photodetector array with the capability of recording a simple image produced by NIR illumination and monitoring a moving photonic signal, showing the great possibility for NIR image sensing and light trajectory tracking applications.